Απόφαση συνεδρίασης του Δημοτικού Συμβουλίου Κοζάνης για την αποζημίωση πυρκαγιάς του καταστήματος Νικ.Γκουζγκούνη
Απόφαση συνεδρίασης του Δημοτικού Συμβουλίου Κοζάνης για την αποζημίωση πυρκαγιάς του καταστήματος Νικ.Γκουζγκούνη